The Impact of HPV on Young Women’s Health: The Role of Nursing (Research, Society and Development, 2026)
Introduction: Human Papillomavirus infection is the most common sexually transmitted infection in the world. It is estimated that approximately 80% of the sexually active population is exposed to the virus, which is associated with more than 90% of cervical cancer cases, representing one of the main impacts on the health of young women. Therefore, nurses play an essential role in guidance and prevention. Objective: To analyze the main consequences of HPV on the health of young women; to describe women's perceptions of HPV, its transmission, and prevention; and to report women's perceptions of the role of nursing in HPV guidance and prevention. Method: A qualitative-quantitative and descriptive field study was conducted in 2025 with 170 women using an electronic questionnaire. Results: Although most had prior knowledge about HPV, gaps persist in understanding its transmission and prevention methods. It was observed that HPV impacts physical health and emotional well-being, triggering fear, insecurity, and stigma, mainly due to its association with cancer and infertility. The role of nursing as an agent of social transformation was highlighted, promoting support, active listening, and information. Conclusion: The study showed that the emotional impact transcends the physical, directly interfering with self-image and the experience of sexuality. The importance of nursing through support, active listening, and educational strategies that promote adherence to preventive practices and female self-care is emphasized.